'More, better, faster & sustained': Strengthen primary health care to advance universal health coverage - Lahariya, Chandrakant (Indian journal of medical research (New Delhi, India : 1994), 2019)
UHC has laudable and widely understood objective of 'Universal Health' with 'Coverage' in all three dimensions [1],[3], namely: (i) a wide range of quality services delivered through health systems having strong foundation of comprehensive primary healthcare; (ii) all populations, with focus on leaving no one behind, keeping equity and social justice as principles; and (iii) appropriate mechanisms are in place to ensure financial protection while people access health services they need. Health is a State subject in India, and in urban settings, elected local bodies are responsible for primary care and public health services. [...]the singular reliance on union government initiative would not be enough. [...]PHC for all' starts with better measurements, and strengthening monitoring systems for PHC and UHC will guide the corrective actions and accelerate progress. [...]progress on PHC and UHC would be dependent on additional evidence generated, and it would need institutionalized mechanisms, at both national and sub-national level, for implementation research and capacity building of relevant stakeholders, supported by sufficient government funding for both [32].